PENGGUNAAN TUTURAN IMPERATIF DALAM ACARA TELEVISI TRANS7 LAPOR PAK EPISODDE COKI ANWAR - Mashuri, Fajar Ali; Nugrahani, Farida; ., Sukarno (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2023)
This study aims to describe the form of imperative speech and describe the form of imperative pragmatics in the television program report sir! coki anwar episodes. This study used descriptive qualitative method. The source of this research is in the form of dialogue between players or artists in television shows, report sir!. The data in this study are in the form of imperative utterances used by players or artists in the Report Pak! Coki Anwar episode. The research data collection technique was carried out using documentation techniques, watch and record, this technique begins with downloading a video rebroadcast at the report sir event! Coki Anwar episode. Then intensive listening techniques are carried out to bring up the data, the next step is to transcribe the data into writing. The final stage is to classify data according to category and type. The results of this study can be concluded at the report sir! In the Coki Anwar episode, there are 17 formal and varied imperatives with details, 5 request imperatives, 3 imperative imperatives, 4 ordinary imperatives and 5 imperative imperatives. There are 17 imperative pragmatic forms found but less varied with details of 3 imperative orders, 4 imperative imperatives, 2 imperative imperatives, 4 imperative imperatives of prohibition, 2 imperative imperatives, 1 imperative imperative and 1 plea. The total imperative utterances contained in the report report sir! There are 34 episodes of Coki Anwar.